Ameloblasts in health and disease - Sandhya Tamgadge; Avinash Tamgadge; Bhagyashree Agre (Wolters Kluwer Medknow Publications, 2021)
Ameloblasts are highly sensitive enamel-forming cells. They are derived from ectoderm and undergo a series of transformative changes in their life cycle. The functional efficiency of ameloblasts depends on various factors such as intracellular and extracellular environment, epithelial-mesenchymal interactions, and genetic control. Enamel formation is a well-organized event in the life cycle of ameloblasts. Normal enamel formation is the sign of healthy ameloblasts. The well-being of ameloblasts would be under threat in multiple situations. Internal regulatory mechanisms that are influenced by genetic mutations will lead to abnormal behavior of the cell. Environmental factors such as trauma, infection, exposure to chemicals, nutritional deficiencies, and hormonal dysregulation would affect the cell's normal behavior, which leads to abnormal enamel production. In this article, factors affecting the health of ameloblasts are described briefly.